2010
DOI: 10.1177/0003319709360526
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Abdominal Aortic Aneurysm (AAA) Growth and AAA Rupture Risk Besides AAA Size: Fact or Fiction?

Abstract: Flondell-Sité et al in this issue of Angiology report that besides abdominal aortic aneurysm (AAA) diameter (P ¼ .0019), endothelin-1 (ET-1) levels (P ¼ .0230) were significant predictors of AAA growth in 178 patients with AAA followed conservatively (mean: 2.9 + 1.6 years).1 In univariate analysis, ET-1 levels also predicted death or need for AAA surgery.1 These results suggest an alternative/additional predictor of AAA growth and rupture risk besides AAA diameter.Currently, the main criterion for AAA repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…6 In recent years, some adjunctive treatments such as hyperbaric oxygen have been shown to not only improve the healing rate of diabetic foot wounds, but also reduce amputation rates. 7 Hyperbaric oxygen therapy (HBOT) involves breathing pure oxygen in a hyperbaric chamber at more than one atmosphere of pressure, which passively raises oxygen tension in arteries and tissues. 8 It has been found that hyperbaric oxygen improves vascular blood flow in the lower limbs of patients, promotes local blood and oxygen supply, improves neuropathy in the tissues surrounding the diabetic foot, enhances tissue metabolism, reduces inflammatory exudation and reduces or eliminates oedema, thus accelerating ulcer healing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In recent years, some adjunctive treatments such as hyperbaric oxygen have been shown to not only improve the healing rate of diabetic foot wounds, but also reduce amputation rates. 7 Hyperbaric oxygen therapy (HBOT) involves breathing pure oxygen in a hyperbaric chamber at more than one atmosphere of pressure, which passively raises oxygen tension in arteries and tissues. 8 It has been found that hyperbaric oxygen improves vascular blood flow in the lower limbs of patients, promotes local blood and oxygen supply, improves neuropathy in the tissues surrounding the diabetic foot, enhances tissue metabolism, reduces inflammatory exudation and reduces or eliminates oedema, thus accelerating ulcer healing.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, diabetic foot treatments have included the administration of improved microcirculation, proper control of blood glucose levels, regular local debridement and dressing changes, anti‐infection, nerve nutrition and amputation 6 . In recent years, some adjunctive treatments such as hyperbaric oxygen have been shown to not only improve the healing rate of diabetic foot wounds, but also reduce amputation rates 7 . Hyperbaric oxygen therapy (HBOT) involves breathing pure oxygen in a hyperbaric chamber at more than one atmosphere of pressure, which passively raises oxygen tension in arteries and tissues 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This Editorial discusses AAA geometrical parameters and peak wall stress as the potential predictors of AAA growth and rupture risk. 9 Identifying the Problem Abdominal aortic aneurysm is largely a disease of elderly men, being 2 to 6 times more common in males than in females. 10 It appears in men around the age of 50 and reaches a peak incidence near the age of 80, whereas in women the onset of the disease is more delayed, following a steady increase thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…Increased 18F-FDG uptake in AAAs is associated with inflammation, aortic wall instability, and rupture risk [ 6 ]. Therefore, 18F-FDG uptake might be a new technique to study AAA disease in vivo and may improve prediction of AAA rupture risk [ 6 , 7 ]. The prognostic value of 18F-FDG uptake was verified by a study reporting increased focal uptake of 18F-FDG in patients with large, rapidly expanding, or symptomatic AAAs that are prone to rupture [ 8 ].…”
mentioning
confidence: 99%